Student Motivation and Literacy about Start Up Business (Case Study in Business Administration Department of Bengkalis State Polytechnic) - Rini Arvika Sari; Supriati (International ABEC, 2022)
This study aims to determine Student Motivation and Literacy Regarding Start Up Business in the Department of Business Administration, Bengkalis State Polytechnic. This research is categorized as a quantitative descriptive study with a population of students majoring in business. Determination of the sample using the technique of Snowball Sampling and obtained as many as 100 students. The data obtained through the distribution of questionnaires with a Likert scale. The analytical technique used is quantitative descriptive analysis. The results showed that 52% of student literacy in start-up businesses was in the high category, 42% in the medium category and 35% in the low category. As for the motivation in the high category as much as 73%, in the medium category as much as 55%, and in the low category as much as 53%.